Dari Tradisi ke Transaksi: Merancang Ekosistem Kewirausahaan Digital yang Berlandaskan Filosofis bagi Pesantren Indonesia - Anas Alhifni; Radif Khotamir Rusli; Martin Roestamy; Biyati Ahwarumi (JURNAL ILMIAH GEMA PERENCANA, 2026)
The global digital economy presents a formidable challenge to traditional institutions, demanding a paradigm shift that balances cultural preservation with economic innovation. This study investigates the construction of an ethical and sustainable Digital Entrepreneurial Ecosystem (DEE) for Indonesian Islamic boarding schools (pesantren), institutions central to the nation’s social and religious fabric. Grounded in a philosophical synthesis of Indonesia’s People’s Economy (Ekonomi Kerakyatan) principles and Islamic ethics, this research addresses the critical nexus of traditional values and modern digital transactional demands. Employing a qualitative multi-case study of five influential pesantren in East Java, the research identifies the core components and strategic pathways for this digital transition. The findings reveal that a successful ecosystem architecture rests on three pillars: Ethical-Spiritual Governance, leveraging the moral authority of leadership (Kyai) and community trust; Socio-Digital Collaboration, which translates immense social capital into structured digital networks; and Inclusive Capacity Building, which creates accessible pathways for digital literacy and entrepreneurship. This study critiques the conventional technology-centric ecosystem models, proposing a novel, values-driven framework that positions pesantren as architects of a more equitable and culturally resonant digital future. It contributes a philosophically robust model for digital entrepreneurship that prioritizes holistic community welfare (falah) over profit-centric metrics, offering a significant contribution to the discourse on ethical technology adoption in religious communities.